The Relevance of Biblical Exegesis to the Study of the Dynamics of the Educational Relationship in Contemporary Pedagogy. An Example of the Biblical Story of the Calling of Levi - Waga, Leszek (Paedagogia Christiana, 2025)
Pedagogues analysing the role of theology in pedagogical sciences often see theology as the basis for making moral recommendations derived primarily from the Revelation contained in the Bible. This approach minimises the relevance of biblical sciences to pedagogy while narrowing the perspective of its research areas. Biblical exegesis is now revealing a number of issues of great importance for contemporary pedagogy. One of these is the dynamics of the educational relationship, especially the mutual influence and role of the educator and the student in the educational process. The main focus of this article’s analysis is the Gospel story of the calling of Levi (Matthew) and Jesus’ subsequent meal with sinners and tax collectors. The interpretative possibilities of this story, or rather of the one sentence linking the calling with the description of the meal (Mark 2:15), will be presented in the light of contemporary possibilities of biblical exegesis. The results of biblical studies do not conclusively resolve the question of whether, after the calling, the disciple followed the Master or the Master followed the disciple. This issue may be a symbolic exemplification of the problem of the subjectivity of the educator and the student in their educational relationship. The article deals with the meta-theoretical issue of pedagogy, demonstrating new possibilities for the use of biblical teachings in pedagogy. The aim of the study is to show close links between the dilemmas of contemporary biblical exegesis and issues of education. Sources for the analyses carried out include publications in the field of biblical exegesis as well as monographs and articles from the field of general pedagogy (concerning interdisciplinary research as well as the language of pedagogy) and Christian pedagogy.